Actin stress fiber organization promotes cell stiffening and proliferation of pre-invasive breast cancer cells - Tavares, Sandra; Vieira, Andre Filipe; Taubenberger, Anna Verena; Araujo, Margarida; Martins, Nuno Pimpao; Bras-Pereira, Catarina; Polonia, Antonio; Herbig, Maik; Barreto, Clara; Otto, Oliver; Cardoso, Joana; Pereira-Leal, Jose B.; et al. (Nature Communications, 2017)
Studies of the role of actin in tumour progression have highlighted its key contribution in cell softening associated with cell invasion. Here, using a human breast cell line with conditional Src induction, we demonstrate that cells undergo a stiffening state prior to acquiring malignant features. This state is characterized by the transient accumulation of stress fibres and upregulation of Ena/VASP-like (EVL). EVL, in turn, organizes stress fibres leading to transient cell stiffening, ERK-dependent cell proliferation, as well as enhancement of Src activation and progression towards a fully transformed state. Accordingly, EVL accumulates predominantly in premalignant breast lesions and is required for Src-induced epithelial overgrowth in Drosophila. While cell softening allows for cancer cell invasion, our work reveals that stress fibre-mediated cell stiffening could drive tumour growth during premalignant stages. A careful consideration of the mechanical properties of tumour cells could therefore offer new avenues of exploration when designing cancer-targeting therapies.
CRIS-Team Scopus Importer:2022-08-05